Experiências vividas no ensino e subjetividades imanentes configurando o perfil dos professores de Educação Física da educação infantil nas escolas municipais de Cuiabá-MT - Lúcio, Géssica Adriana de Carvalho (2017)
The intention of the research is to investigate the research that is based on the profile of Physical Education teachers, with emphasis on the exercise in teaching teaching and in teaching experiences with Early Childhood Education. Its main objective is to characterize a profile of Physical Education teachers with emphasis on their experiences with Early Childhood Education in the municipal schools of Cuiabá-MT. Being a field study, descriptive in nature, with a qualitative and interpretive approach, the subjects of the research were the Physical Education teachers of the municipal schools of Cuiabá-MT, who work in Early Childhood Education. The sample consisted of 50 teachers who answered a questionnaire and, subsequently, selected 10 teachers who participated in the interview. The questionnaire was divided into categories containing open and closed questions. The categories were divided into: identification data (age, sex, employment status), career choice, vocational training, work in school, pedagogical practice on teaching in infant education and, finally, continuing education. The interview focused on the most significant teaching experiences developed at this level of education. Data analysis was performed using the coding categories system (BOGDAN; BIKLEN, 1994). The interpretation of the information obtained by the instruments went through content analysis (BARDIN, 1977). The investigative course allowed us to better understand the current reality of Physical Education in Early Childhood Education in the city of Cuiabá, knowing a little about the profile of the subjects and their experiences with this age group. It is evidenced that there is still a significant weakness in the formation of these Physical Education teachers, related to the necessary knowledge and skills to perform in Early Childhood Education. We observed that even with the weaknesses in the training, these subjects seek to overcome the problems of origin. Physical Education teachers are in a process of building their identity as a child education professional, if it is necessary to look at and rethink the initial formation of this teacher, because they need to learn how to deal with the situations arising from praxis in this age group, recalling that teacher training is an ongoing process that requires constant revision. From the conceptions of experiences found in the answers of the subjects-teachers mediated by the movement of Practice + Theory we elaborate the typology, where in our empirical universe from the evidences found in the answers of the subjects of the research we classify based on their manifestations with which typology and author approach in three groups, based on the concepts related to the experience of authors as: Georg Gadamer (2008) those who conceive the experience as something that is renewed in the clash with the reality of the practice; Walter Benjamim (1994) those who conceive the experience as a universal collective tradition, however re-signified and Boaventura de Souza Santos (2007) the indolent or lazy experience of reinventing itself in day to day with social practice. If experience is something that makes more relation to the present lived than to the future, still as a becoming, it seems that the profile of teachers can be related to the idea of the present being permeated by the possibility of already being living an eternal "Not yet". We can glimpse a new outline, inasmuch as experience is something that is taking shape in the actions of the subject-teachers with their child-bodies in which teaching can be losing the primacy over learning.